Structural Patching Fosters Divergence of Mitochondrial Ribosomes. (4th December 2018) - Petrov, Anton S; Wood, Elizabeth C; Bernier, Chad R; Norris, Ashlyn M; Brown, Alan; Amunts, Alexey
Abstract: Mitochondrial ribosomes (mitoribosomes) are essential components of all mitochondria that synthesize proteins encoded by the mitochondrial genome. Unlike other ribosomes, mitoribosomes are highly variable across species. The basis for this diversity is not known. Here, we examine the composition and evolutionary history of mitoribosomes across the phylogenetic tree by combining three-dimensional structural information with a comparative analysis of the secondary structures of mitochondrial rRNAs (mt-rRNAs) and available proteomic data. We generate a map of the acquisition of structural variation and reconstruct the fundamental stages that shaped the evolution of the mitoribosomal large subunit and led to this diversity. Our analysis suggests a critical role for ablation and expansion of rapidly evolving mt-rRNA. These changes cause structural instabilities that are "patched" by the acquisition of pre-existing compensatory elements, thus providing opportunities for rapid evolution. This mechanism underlies the incorporation of mt-tRNA into the central protuberance of the mammalian mitoribosome, and the altered path of the polypeptide exit tunnel of the yeast mitoribosome. We propose that since the toolkits of elements utilized for structural patching differ between mitochondria of different species, it fosters the growing divergence of mitoribosomes.